The Effect of Market Orientation on the Performance of Small and Medium Enterprises in Case of Amhara Region, Ethiopia. Issue 1 (June 2020) - Hassen, Yissa; Singh, Amanpreet
The study investigated the effect of market orientation on the performance of small and medium enterprises in case of Amhara Region, Ethiopia. Primary data was collected from a total of 250 owners/managers of small and medium enterprises using structured questionnaire. A multivariate data analysis technique of structural equation modelling was employed to analyse the data. The result indicated that customer orientation and interfunctional coordination dimensions of MO are significantly and positively affected small and medium enterprises performance. However, competitor orientation dimension was not found to have a positive and significant effect on the performance. The findings revealed that small and medium enterprises need to be more market oriented to realize superior performance. In addition, the different beta coefficient of market orientation indicated that new business ventures are highly recommended to conduct a market orientation profile and take care in investing their scarce resources. Moreover, the mixed results indicate that firms are advised to replicate market orientation to score superior performance with due care in considering the contexts and time in the industry they are operating and match strategies with their internal resources and core competencies. Finally, this study contributed to the almost wholly overlooked research on market orientation and performance linkages in Ethiopian case and the empirical context of this study is quite novel and helpful for developed nations firms who are trying to operate in emerging economies such as Ethiopia.